Role of Complement System in Kidney Transplantation: Stepping From Animal Models to Clinical Application - Qi, Ruochen; Qin, Weijun (Frontiers in Immunology, 2022)
Kidney transplantation is a life-saving strategy for patients with end-stage renal diseases. Despite the advances of surgical technique and immunosuppressive agents, the long-term graft survival remains a challenge. Growing evidence have shown that the complement system, part of the innate immune response, is involved in the setting of kidney transplantation. Novel insights highlighted the role of the locally produced, and intracellular complement components in the development of inflammation as well as alloreactive response in kidney allograft. In the current review, we will provide the updated understandings of the complement system in kidney transplantation. We will discuss the involvement of different complement components in kidney ischemia-reperfusion injury, delayed graft function, allograft rejection and chronic allograft injury. We will also introduce the existing as well as upcoming attempts to improve allograft outcome in animal models and in clinical setting by targeting the complement system.